The natural soap chef : making luxurious delights from cucumber melon and almond cookie to chai tea and espresso forte - Barto, Heidi Corley (Ulysses Press, 2012)
Provides instructions for making all-natural, gentle soaps that cleanse and soothe skin utilizing an old-fashioned cold process using lye and oil that can be customized with scents and herbs into signature, personal creations --